Drug resistance patterns, trends, and risk factors for multidrug resistance of tuberculosis in Wenzhou, China: a ten-year retrospective analysis (2014–2023) - Wu, Lianpeng; Xia, Dandan; Xu, Shuya; Lin, Xuefeng; Peng, Tingting; Jiang, Xiangao (Frontiers in Medicine, 2025)
ObjectiveTuberculosis (TB), particularly drug-resistant tuberculosis (DR-TB), remains a major public health threat in China. Despite global efforts, multidrug-resistant tuberculosis (MDR-TB) complicates control strategies. Wenzhou, a densely populated coastal city, lacks localized data on TB drug resistance trends. This study analyzes DR-TB patterns (2014–2023) and identifies MDR-TB risk factors to inform targeted interventions.MethodsA retrospective study included 10,993 TB patients from Wenzhou Central Hospital. Sociodemographic and phenotypic drug susceptibility testing (pDST) data were extracted from the Tuberculosis Information Management System (TBIMS) of the Chinese Center for Disease Control and Prevention (China CDC) and hospital databases. Resistance definitions followed World Health Organization criteria. Trends in resistance rates and risk factors for MDR-TB were evaluated using chi-square tests and multivariate logistic regression.ResultsAmong 10,993 patients, 20.41% had DR-TB. Resistance rates in new patients were highest for isoniazid (12.15%) and streptomycin (10.89%), while retreated patients showed higher resistance to isoniazid (34.61%) and rifampicin (27.04%). The overall drug resistance rate of DR-TB decreased from 26.01% (2014) to 19.31% (2023), driven by a decline in retreated cases (64.19%–28.57%), whereas the proportion in new cases remained stable (∼18%). The proportion of MDR-TB in retreated patients fell from 47.30% to 18.37%, but increased slightly in new cases (2.51%–3.86%). Risk factors for MDR-TB included age <65 years (OR = 1.496–1.640), Han ethnicity (OR = 1.911), migrant status (OR = 1.296), unemployment (OR = 1.819), and prior TB treatment (OR = 7.513).ConclusionDrug-resistant tuberculosis prevalence in Wenzhou declined over the decade, largely due to improved management of retreated cases. However, persistent primary DR-TB transmission among new patients highlights the need for enhanced active screening and targeted interventions. High-risk groups, including young people, individuals of Han ethnicity, migrants, unemployed individuals, and retreated patients, require prioritized attention in TB control strategies.